2010
DOI: 10.1109/tgrs.2009.2027699
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of the Aerosol Extinction-to-Backscatter Ratio from Sun-Photometric Measurements

Abstract: Abstract-The elastic lidar equation contains two unknown atmospheric parameters, namely, the particulate optical extinction and backscatter coefficients, which are related through the lidar ratio (i.e., the particulate-extinction-to-backscatter ratio).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“… Müller et al [2007] summarize a set of field campaigns, in which S at 532 nm was found to be from 23–29 for marine aerosol. Pedrós et al [2010] obtained median values of S at 532 nm of 31, 36, and 37 for air masses originating from different oceanic regions, although there may have been a local contribution to these results. The AERONET analysis of Smirnov et al [2003a] at Lanai gives 34.5 at 500 nm and 37 at 1020 nm.…”
Section: Lidar Ratiosmentioning
confidence: 78%
See 1 more Smart Citation
“… Müller et al [2007] summarize a set of field campaigns, in which S at 532 nm was found to be from 23–29 for marine aerosol. Pedrós et al [2010] obtained median values of S at 532 nm of 31, 36, and 37 for air masses originating from different oceanic regions, although there may have been a local contribution to these results. The AERONET analysis of Smirnov et al [2003a] at Lanai gives 34.5 at 500 nm and 37 at 1020 nm.…”
Section: Lidar Ratiosmentioning
confidence: 78%
“…where P, the scattering phase function, is typically normalized to integrate to either 1 or 4p, and w 0 is the aerosol single scattering albedo; i.e., S is simply the ratio of total extinction to backscatter. As such for a given vertically-integrated backscatter, the calculated AOD is directly proportional to S. Depending on the characteristics of an individual lidar, S is either calculated from measured extinction and backscatter (for example, Pedrós et al [2010]), or prescribed as a function of aerosol type. In the latter situation the choice of an appropriate S is therefore important for the accurate calculation of aerosol loading.…”
Section: Lidar Ratiosmentioning
confidence: 99%
“…They can complement the sunphotometer measurements by providing height-dependent measurements and helping to determine the aerosol characteristics at various heights of the atmospheric column (Mattis et al, 2004). Various research endeavors have been conducted by synergizing the LIDAR measurements with the sunphotometer measurements (Chazette, 2003;Pedrós et al, 2010). However, results from this approach poorly resemble the actual atmospheric conditions, as only a single-valued, range-independent atmospheric parameter is obtained, such as the LIDAR ratio, while in fact, there might be several atmospheric layers that exist in the atmosphere (Royer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus the AODs obtained by these two methods are compared, and a lidar ratio value is selected when the differences are minimized [ Guerrero ‐ Rascado et al , 2008]. According to Pedrós et al [2009], a worst case estimate of the uncertainty associated with the lidar ratio is 10%. After deriving the backscatter coefficient profiles using the appropriate lidar ratio, we compute other properties such as the backscatter‐related Ångström exponent profiles.…”
Section: Methodsmentioning
confidence: 99%